Erectile Dysfunction and Correlates Among Diabetic Men at Dessie Referral Hospital: North Central Ethiopia, 2020 - Abeway S (Dove Medical Press, 2020)
Shiferaw Abeway,1 Kefyalew Dagne,2,3 Tazeb Zegeye4 1School of Nursing and Midwifery, Department of Pediatric and Child Health Nursing, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Department of Psychiatry, College of Health Sciences and Medicine, Debre Berhan University, Debre Berhan, Ethiopia; 3Department of Psychiatry, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 4School of Medicine, College of Medicine and Health Science, Wollo University, Dessie, EthiopiaCorrespondence: Shiferaw AbewaySchool of Nursing and Midwifery, Department of Pediatric and Child Health Nursing, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaTel +251931614769Email shifeby@gmail.comBackground: Erectile dysfunction is currently one of the most common sexual dysfunctions worldwide affecting the quality of life of men of all ages, but it is usually underestimated because it is not a life threatening condition.Purpose: This study aims to determine the prevalence of erectile dysfunction and the possible correlates among diabetic men in Dessie Referral Hospital, North Central Ethiopia.Methods: An institution-based cross-sectional study was conducted among diabetic men aged greater than 18 years, at Dessie Referral Hospital. Systematic random sampling technique was used to select study participants. A pre-tested and structured questionnaire was used to collect the data. Data were entered in Epi Info version 7 and analyzed using SPSS version 21. Logistic regression was applied to identify association between explanatory variables and the outcome variable. An adjusted odds ratio with 95% confidence interval and p-value less than 0.05 was computed to determine the level of significance.Results: Overall, the prevalence of erectile dysfunction (ED) in this study was 58.5% at 95% CI (0.548– 0.622), and specifically 10.5%, 40.9%, 6.8% respondents had mild, moderate and severe erectile dysfunction, respectively. Age, duration of diabetes diagnosis, types of medication, types of complication and body mass index were significant unadjusted factors associated with erectile dysfunction, but following adjustment only age [AOR=5.5 (95% CI 2.06– 14.744), duration of diabetes [AOR=20,(95% CI 5.663– 75.0096) and types of medication [AOR=2.106 (95% CI 1.112– 3.988) have independently statistically significant association with erectile dysfunction.Conclusion: This study showed that ED is high. Age, duration of diabetes mellitus and type of medication are independently associated with erectile dysfunction. Health policymakers need to consider including the training of health personnel to consider the relevant risk factors during the physical, social and psychological assessment of patients, and clinicians should pay attention to the sexual history of their client.Keywords: diabetes, erectile dysfunction, Dessie